Effects of Carbohydrates on in vitro axillary shoot initiation and multiplication of Bambusa pallida Munro. - B, Beena D; S, Rathore T; S, Rao P (Journal of Phytology, 2013)
The purpose of the current study was to optimize the carbohydrate sources and sucrose concentrations for mass clonal propagation of B. pallida. Sucrose in MS liquid medium consisting additives (ascorbic acid, 50mg/l + citric acid, 25 mg/l + cysteine, 25 mg/l) was found to be the best carbohydrate source for shoot induction and shoot multiplication. NAA 0.25mg/l in combination with TDZ 0.25mg/l in the medium exhibited high frequency shoot induction and NAA 0.25mg/l with BAP 1.0mg/l helped for further multiplication of quality shoots. IBA pulse treated shoots were rooted in the MS half strength agar gelled medium fortified with sucrose (2%) and glucose (1%). Rooted plantlets were well established in the green house with more than 95% survivability within four weeks period.